Implementasi Putusan Mahkamah Konstitusi tentang Hak Konstitusi Bagi Penganut Kepercayaan terhadap Tuhan Yang Maha Esa - Muchimah Muchimah; Muh. Bachrul Ulum (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This paper aims to find out the constitutional rights of the Believers of the Almighty God before the Decision of the Constitutional Court and the Implementation of the Constitutional right after the Decision of the Constitutional Court. This paper is a field research conducted in Banyumas Regency in 2019. The approach uses in this research is sociological- normative with descriptive analysis methods in analyzing data. The results of this study prove that the decision has been implemented as a form of implementation in fulfilling the constitutional rights of the Believers of the Almighty God in Banyumas Regency as stated in their ID card that their religion is Believers of the Almighty God.